Non-invasive diagnosis of liver fibrosis in patients with alcohol-related liver disease by transient elastography: an individual patient data meta-analysis - Nguyen-Khac, Eric; Thiele, Maja; Voican, Cosmin; Nahon, Pierre; Moreno, Christophe; Boursier, Jerome; Mueller, Sebastian; de Ledinghen, Victor; Stärkel, Peter; Gyune Kim, Sang; Fernandez, Michael; Madsen, Bjorn; et al. (The lancet. Gastroenterology & Hepatology, 2018)
Background - The value of transient elastography for the non-invasive diagnosis of alcohol-related liver fibrosis is subject to debate. We did an individual patient data (IPD) meta-analysis to determine specific diagnostic cutoff values for liver stiffness in alcohol-related fibrosis, and to assess the effect of aminotransferase concentrations, bilirubin concentrations, and presence of asymptomatic and non-severe alcoholic hepatitis on liver stiffness. - Methods - We searched for studies that included patients with alcohol-related liver disease, liver biopsy, and transient elastography, and with a statistical method for determining the diagnostic cutoffs for alcohol-induced liver fibrosis on the basis of the FibroScan results, in PubMed between Jan 1, 2000, and Sept 30, 2017. Native data bases were obtained from corresponding authors in an Excel form. Pooled diagnostic cutoffs for the various fibrosis stages were determined in a two-stage, random-effects meta-analysis. The effects of aspartate aminotransferase (AST) concentrations, bilirubin concentrations, and histological features of asymptomatic and non-severe alcoholic hepatitis on liver stiffness cutoff were assessed in one-stage, random-effects meta-analysis. - Findings - Of 188 studies assessed, ten studies comprising 1026 patients were included in the meta-analysis, yielded liver stiffness cutoffs of 7·0 kPa (area under the receiver operating characteristic curve 0·83 [SE 0·02; 95% CI 0·79-0·87]) for F≥1 fibrosis, 9·0 kPa (0·86 [0·02; 0·82-0·90]) for F≥2, 12·1 kPa (0·90 [0·02; 0·86-0·94]) for F≥3, and 18·6 kPa (0·91 [0·04; 0·83-0·99]) for F=4. AST and bilirubin concentrations had a significant effect on liver stiffness, with higher concentrations associated with higher liver stiffness values (p<0·0001), and with significantly higher cutoff values for diagnosis of all fibrosis stages but F≥1. The presence of histological features of asymptomatic and non-severe alcoholic hepatitis was associated with increased liver stiffness (p<0·0001). In a multivariate analysis, AST (p<0·0001) and bilirubin (p=0·0002) concentrations, and prothrombin activity (p=0·01), were independently associated with the presence of histological features of asymptomatic and non-severe alcoholic hepatitis. Lastly, specific liver stiffness cutoffs were determined on the basis of concentrations of AST and bilirubin. Liver stiffness cutoff values increased in patients with increased AST concentrations, bilirubin concentrations, or both. - Interpretation - This IPD meta-analysis highlights the link between liver stiffness and the histological features of asymptomatic and non-severe alcoholic hepatitis, reflected by AST and bilirubin concentrations. In alcohol-related liver disease, FibroScan assessments of liver fibrosis should take into account AST and bilirubin concentrations through the use of specifically adjusted liver stiffness cutoffs. - Funding - None.